International journal of distributed systems and technologies - IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
"The International Journal of Distributed Systems and Technologies (IJDST) focuses on integration techniques, methods, and tools employed in applied distributed computing systems, architectures, and technologies. IJDST pays particular attention to this dimension as a means of diversifying and broadening the applicability and scope of knowledge in the area of distributed systems and technologies. This journal is dedicated to push developmental boundaries and publish cutting-edge developments related to science-to-science, science-to-business, business-to-business, business-to-customer, and customer-to-customer interactions."--Provided by publisher.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, issue 1 (2010); title from title screen (IGI Global, viewed Oct. 5, 2010).
Latest issue consulted: Vol. 1, issue 3 (2010).
Keywords: Electronic data processing -- Distributed processing -- Periodicals; Computer networks -- Periodicals; Algorithms, software, application, services and technologies integration methods; Process, resource, service and data virtualization, sharing, and integration; Process, resource, service and resource flow management; Science-to-science, science-to-business, business-to-business, business-to-customer, and customer-to-customer models; Geographical information systems; Health informatics; Early warning systems, evacuation processes, climate changes, disaster management, threat detection; E-society, global economies, developing countries, education; Integration methods and tools for performance analysis, verification, testing, benchmarking; Science or business process, models, and application integration and management; Operational research, economic models, supply chain; Collaborative environments including science, engineering, management, business; Forensics, security, cryptography, threat detection, business continuity, trust, identity management, policies, quality of service management; Design and analysis of distributed algorithms, programming languages, compilers, software tools and middleware environments; Autonomy services; Cloud computing; Service oriented, grid, peer-to-peer, throughput and cluster programming interfaces; Scheduling and fault-tolerance service and algorithms; Synchronization and concurrency theory and programming; Matching, mapping, and other novel techniques; Novel algorithms, uses, and implications of distributed systems (internet, wireless communications, mobile, ad-hoc networks, and sensors); Representation techniques (semantics, meta-data, tagging, clouds, ontologies, and knowledge bases); Pervasive and utility computing; Grid, next generation grid, and next generation technologies; Click stream; Data mining; Databases; Data warehouses; Web houses; Web data centers and sites; Mashups; Intra- and inter-tagging; Parallel or integration algorithms; User and community led systems; Human and/or market dynamics influencing decisions and transitions; Electronic books